Susceptibility of Dermatophytes to Thiabendazole Using CLSI Broth Macrodilution - Robledo-Leal, Efrén (International Scholarly Research Network, 2012)
Objective. To evaluate in vitro antifungal activity of thiabendazole against strains of dermatophytes using a reference method for filamentous fungi. Materials and Methods. Dermatophytes' susceptibility to thiabendazole (TBZ) and fluconazole (FCZ) was evaluated using macrodilution method of protocol M38-A2 of the Clinical and Laboratory Standards Institute (CLSI). Results. MIC ranges of TBZ for all strains were narrower and/or smaller than those of FCZ. TBZ showed a significantly greater potency than FCZ (P = 0.05) against all isolates. Discussion. Although there have been approaches to evaluate the antifungal activity of TBZ in human mycoses, no tests had been made with a standardized protocol. Susceptibility data resulted from this study shows that although TBZ is not a particularly strong inhibitor of dermatophytes, it displays a stable and constant effect against all isolates tested. Conclusion. Results show that TBZ is more effective against strains of dermatophytes than FCZ. We acknowledge the antifungal effect of TBZ against dermatophyte isolates.